(untitled) (International Journal on Stereo & Immersive Media, 2025)
Coined in the 1790s, the term “panorama” originally described a purpose-built rotunda containing a circular painting that immersed viewers in a depicted place or event. Though presently understood as fixed in their locations, panoramas were typically designed to be circulated. This was accomplished either by transporting the canvas between rotundas, or by moving the entire structure, either way subjecting them to wear and tear. Surviving heritage examples endured in part because they became stationary exhibits; but whether mobile or fixed, the geographic location of display was—and, importantly, remains—intrinsic to their meaning. Panoramas are geographic documents that combine painting, architecture, lighting, and visitor movement to create an illusion of scale, aligning—or productively misaligning—subject and site in space and time. Recognition in UNESCO’s Memory of the World Program would bring attention to an archive that is geographically distributed rather than institutionally centralized. The International Panorama Council is uniquely qualified to define and interpret a dispersed archive that invites critical engagement with place-based histories of visitation, visualization, political formation, and the built environment.